A 50-Year Overview of the Coronavirus Family with Science Mapping Techniques: A Review - Ayhan Tabur; ALİ Arslanoğlu (Tehran University of Medical Sciences, 2021)
Background: The COVID-19 pandemic from the coronavirus family is the most important agenda of today's world, also called the "New World". In this outbreak period, declared a pandemic by WHO and affected the whole world and humanity on a global scale, all kinds of scientific information and evidence-based sharing on the subject gained great importance. Methods: Overall, 12,301 articles from the web of Science (WOS) Core Collection database were analyzed using SciMAT software, conducted to examine the development of coronavirus publications in the process and to reveal the scientific mapping related to the subject. To analyze the development in the process based on periods, the articles covering the 50 years were compared as five periods of 10 years. Results: The most publications with the Coronavirus theme were made between 2010 and 2020 (n=1020), the total number of citations of these articles was 15,966 and the h-index value was 54. The theme "Coronavirus" was associated with the themes "infection" (w=0.04), "SARS" (w=0.03), "virus" (w=0.04), "identification" (w=0.05) and "swine" (w=0.03). Due to the recent emergence of the COVID-19 theme, it was found to be directly related to the "outbreak" theme (w=0.01). In terms of the distribution of the articles on coronavirus by country, most articles were published by the USA. This country is followed by China, Germany, England and the Netherlands. Conclusion: This research on the coronavirus family can offer a holistic view of the virus family in the scientific world and can make a scientific contribution to the fight against the virus by creating awareness on this issue.